Pengalaman Orang Tua Dalam Proses Pendampingan Pembelajaran Daring di Masa Pandemi - Ibnu Mutaqin; Mutia Rahmi Pratiwi (Program Studi Komunikasi Fakultas Ilmu Sosial dan Ilmu Politik Universitas Mulawarman, 2021)
Distance learning (PJJ) or online learning is becoming a new story in the life of parenting at home. The problem in the domestic realm regarding the role of parents is interesting to study based on the diversity of experiences of parents as a substitute for teachers at home. This study aims to describe the experiences of parents in implementing parenting during the online learning process during a pandemic. This type of research is qualitative with the phenomenological method. The number of informants was four mothers who have children in elementary school. The results showed that the communication patterns used by parents were democratic and autorative. Informants stated that children felt more comfortable going through the online learning process when parents applied open and two-way communication. All informants also performed their role as substitutes for teachers at home, facilitators, motivators and directors during the online learning process.